2015
DOI: 10.3748/wjg.v21.i18.5654
|View full text |Cite
|
Sign up to set email alerts
|

Ascites and alpha-fetoprotein improve prognostic performance of Barcelona Clinic Liver Cancer staging

Abstract: Adding AFP and ascites to the BCLC staging classification can improve prognosis prediction for early and intermediate stages of hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
4
7
0
Order By: Relevance
“…The current research showed that a high AFP level is an independent risk factor for RFS in patients with HCC who received combined therapies, which was in agreement with Yang et al’s conclusion [20]. The elevated AFP level may be an indication of vascular invasion and HCC progression, both of which contribute to an elevated risk for early recurrence [21].…”
Section: Discussionsupporting
confidence: 89%
“…The current research showed that a high AFP level is an independent risk factor for RFS in patients with HCC who received combined therapies, which was in agreement with Yang et al’s conclusion [20]. The elevated AFP level may be an indication of vascular invasion and HCC progression, both of which contribute to an elevated risk for early recurrence [21].…”
Section: Discussionsupporting
confidence: 89%
“…In the early pathogenesis of DEN induced HCC, the mRNA expression of Epcam and Afp was continuously upregulated in all DEN treated mice compared to saline control (Figure 2A, B (Fig. 2) ), strengthening the evidence for these characteristics as good markers of carcinogenesis (Chan et al, 2014[ 5 ]; Gomaa et al, 2015[ 13 ]). While no time dependent, PHD 2 haplodefiency- relate effect could be observed concerning Epcam mRNA expression (Figure 2A (Fig.…”
Section: Resultssupporting
confidence: 55%
“…We found that Afp and Epcam mRNA expression was continuously upregulated, in all DEN treated mice, at all observed time points. Indeed, Afp and Epcam have been shown to be expressed in hepatocytes during embryogenesis and in cirrhotic and cancerous livers (de Boer et al, 1999[ 7 ]; Ruck et al, 2000[ 32 ]; Yamashita et al, 2008[ 36 ]; Chan et al, 2014[ 5 ]; Gomaa et al, 2015[ 13 ]). The mRNA expression of CK19, Prom1 peaked after 17 weeks of DEN and coincided with increased expression of HIF target genes.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Second, multiple tumors are the characteristic of multicentric development, which could not be usually detected by an imaging test, with a higher possibility to relapse and metastasize Third, AFP, an independent risk factor for recurrence in the present study, might be an indication of vascular invasion and HCC progression, contributing to an increased risk for early recurrence and is in agreement with Yang's conclusion. 26,27 Then, deposited Fib in tumor tissue, as Abbreviations: AFP, alpha-fetoprotein; APR, albumin-to-prealbumin ratio, the APR was estimated as the albumin divided by the prealbumin. Abbreviations: RFA, radiofrequency ablation; MWA, microwave ablation; AHC, argon-helium cryoablation; HBV, hepatitis B virus; HCV, hepatitis C virus; ALD, alcohol liver disease; ALT, alanine aminotransferase; AST, aspartate aminotransferase; γ-GT, gamma-glutamyltransferase.…”
Section: Discussionmentioning
confidence: 99%